Nuclear Control of the Inflammatory Response in Mammals by Peroxisome Proliferator-Activated Receptors - Stéphane Mandard; David Patsouris (PPAR Research, 2013)
Peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors that play pivotal roles in the regulation of a very large number of biological processes including inflammation. Using specific examples, this paper focuses on the interplay between PPARs and innate immunity/inflammation and, when possible, compares it among species. We focus on recent discoveries establishing how inflammation and PPARs interact in the context of obesity-induced inflammation and type 2 diabetes, mostly in mouse and humans. We illustrate that PPARγ ability to alleviate obesity-associated inflammation raises an interesting pharmacologic potential. In the light of recent findings, the protective role of PPARα and PPARβ/δ against the hepatic inflammatory response is also addressed. While PPARs agonists are well-established agents that can treat numerous inflammatory issues in rodents and humans, surprisingly very little has been described in other species. We therefore also review the implication of PPARs in inflammatory bowel disease; acute-phase response; and central, cardiac, and endothelial inflammation and compare it along different species (mainly mouse, rat, human, and pig). In the light of the data available in the literature, there is no doubt that more studies concerning the impact of PPAR ligands in livestock should be undertaken because it may finally raise unconsidered health and sanitary benefits.